Pengaruh Kebutuhan, Harapan, dan Lingkungan Masyarakat Terhadap Motivasi Menjadi Pekerja Migran Indonesia - Ni Made Mia Kharisma Putri; Kadek Rai Suwena (Jurnal Pendidikan Ekonomi Undiksha, 2025)
Employment as a migrant worker had become increasingly popular among the public as a means of improving their economic conditions. This study aimed to analyze the influence of needs, expectations, and the community environment on the motivation to become a Indonesian migrant worker in Buleleng Regency. The research a quantitative approach with multiple linear regression methods. The sample consists of 96 respondents selected through a simple random sampling technique. The result revealed that needs, expectations, and the community environment had a significant influence on the motivation to become a migrant worker. The variable of needs had a positive and significant effect on the motivation to become a migrant worker, as did the variables of expectations and the community environment had a positive and significant effect on the motivation to become a migrant worker. These results indicated that the higher the level of needs and expectations that an individual sought to fulfil, the greater their motivation to work as a migrant worker.